Technological tool for reading comprehension assessment of an argumentative text in Spanish as a native language - Martín Vegas, Rosa Ana; Seseña Gómez, Marta (Texto Livre, 2023)
The cloze procedure, technological tool commonly used to assess reading comprehension in second languages, is not usually used with native speakers. The reasons that rule out this technique with native speakers are based on the fact that it only detects information recognition and microstructural linguistic skills and does not measure global or inferential comprehension of the text. This research questions this idea and, in order to elucidate its procedural value, a tool based on the DELE exam model (level B2) was created and applied to Spanish university students (N=125) with two objectives: 1) to measure the reading comprehension of an argumentative text; 2) to assess the comprehension of discourse coherence and cohesion based on the use of linking words. The tool was designed in Moodle and executed in the classroom. The hit and miss rate of each sentence and connector was measured statistically and the Chi-square test of homogeneity and Cochran's test were applied to assess the significance of the confusion between linking words and argumentative notions. The results show more transparent arguments and linking words and patterns of argumental confusion. It is shown that this cloze-based tool measures the comprehension of argumentative texts in the native language and can be a replicable technological instrument.